Who's buying alcoholic and nonalcoholic beverages (Who's buying series., 2013)
Based on data collected from the Bureau of Labor Statistics' 2010 Consumer Expenditure Survey, this report examines how much Americans spend on both alcoholic and nonalcoholic beverages, all organized by demographics. Also provides data on the "best and biggest" customers, and includes an analysis of spending before and after the Great Recession.